Breeding in Africa for Africa - Mwanga, Robert O.M.; Andrade, M.I.; Carey, T.; Grüneberg, W.J. (2015)
Traditionally, sweetpotato breeding programs have taken a long time, 7 to 8 years, to produce a new variety. Moreover, as of 2008, most countries in Africa had no real breeding program and relied on testing materials developed elsewhere. This flyer explains the work done by 13 active breeding programs in SSA between June 2014 and July 2015 to strengthen conventional sweetpotato breeding, develop accelerated breeding protocols and invest in breeding diverse sweetpotato types to meet the requirements of a wider range of producers and consumers.